Генезис структур и предпосылки усовершенствования трансформаторов и реакторов преобразованием контуров электромагнитных систем (системы с шихтованными и витыми магнитопроводами) - Ставинский, Андрей Андреевич (НТУ "ХПИ", 2011)
Показаны возможности усовершенствования трансформаторов и реакторов на основе пространственных структур аксиальных и радиальных электромагнитных систем, а также шести и восьмигранных образующих контуров катушек обмоток и сечений стержней шихтованных и витых магнитопроводов.

Feasibility of transformers and reactors improvement on the basis of spatial structures of axial and radial electromagnetic systems, as well as hexagonal and octahedral generatrix contours of winding coils and cross-sections of laminated and twisted magnetic circuits bars is shown.
Evolution of structures and preconditions for transformers and reactors improvement via electromagnetic system circuit transformation (systems with laminated and twisted magnetic circuits)
Keywords: энергетические потоки; потери электроэнергии; электростанции; металлоемкость; compact axial and radial electromagnetic systems; laminated and twisted magnetic circuits; transformers and reactors improvement